The penultimate peril - Snicket, Lemony; Helquist, Brett (New York : HarperCollins, 2005)
In this next-to-last chronicle of the lives of the Baudelaire orphans, the siblings pose as concierges at the Hotel Denouement to learn the identities and intentions of certain enemies, encountering characters from their past adventures and pondering the nature of nobility and villainy.
Keywords: Orphans -- Fiction; Brothers and sisters -- Fiction; Hotels, motels, etc. -- Fiction; Disguise -- Fiction; Good and evil -- Fiction; Humorous stories